Collection of figures to explore intra-regime weather variability of North Atlantic-European year-round weather regimes as Supplementary Dataset for Gerighausen et al. (2024) ... - Gerighausen, Judith; Dorrington, Joshua; Osman, Marisol; Grams, Christian (Zenodo, 2024)
This is a supplementary dataset accompanying the publication Gerighausen et al. (2024) submitted to Meteorological Applications. It contains a collection of browsable figures, complementing selected regimes, seasons, and countries in the paper. The figures are provided as a zipped archive. The ZIP-File (1.2 GB) contains 4 subfolders and 4 auxiliary files as described in readme.md in the main folder. Once downloaded and unpacked, the .html navigation panels can be used in any browser to navigate through the plots. Data and methods used to generate the figures are explained in Gerighausen et al. (2024). In brief the analysis is based on ERA5 reanalysis 1979-2021 at 1° grid spacing and 6h temporal resolution aggregated to daily data. Anomalies are computed with respect to a 31-day running mean climatology. The figures are explained in the table below and in the navigation panel. Gerighausen, J., J. Dorrington, M. Osman, and C. M. Grams, 2024: Quantifying intra-regime weather variability for energy applications, ...